Language in Japanese society : - Peng, Fred C. C. (University of Tokyo Press, 1975)
This book consists of the following five parts: sociolinguistics today, description of non-standard varieties, kinship behaviors and la parole of pronouns, language attitudes, language in the transmission of culture.